2022
DOI: 10.1111/jhn.12991
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic use in adults with cystic fibrosis is common and influenced by gastrointestinal health needs: A cross‐sectional survey study

Abstract: Background: Cystic fibrosis (CF) primarily affects the lung, however, gastrointestinal disorders and symptoms, including dysbiosis, also impact on morbidity and quality of life. There is interest in strategies to modulate the gastrointestinal microbiota, including probiotics, although the evidence remains inadequate to guide practice, and information on use is limited. The present study aimed to characterise probiotic use, beliefs and experiences of adults with CF. Methods: A cross-sectional questionnaire stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In a US survey, up to 60% of patients were using a probiotic, 129 and in a similar Australian survey 70% reported to have ever used probiotics. 130 A recent Cochrane Review on the use of probiotics found a significant reduction in faecal calprotectin (a marker of intestinal inflammation) in children and adults with CF. 131 They concluded that some 'likely' benefit exists for probiotic use, but the evidence was considered low certainty.…”
Section: Changing Organ Focusfrom Lung To Gutmentioning
confidence: 99%
See 1 more Smart Citation
“…In a US survey, up to 60% of patients were using a probiotic, 129 and in a similar Australian survey 70% reported to have ever used probiotics. 130 A recent Cochrane Review on the use of probiotics found a significant reduction in faecal calprotectin (a marker of intestinal inflammation) in children and adults with CF. 131 They concluded that some 'likely' benefit exists for probiotic use, but the evidence was considered low certainty.…”
Section: Changing Organ Focusfrom Lung To Gutmentioning
confidence: 99%
“…Another area of interest is the use of pre, pro and synbiotics in this population. In a US survey, up to 60% of patients were using a probiotic, 129 and in a similar Australian survey 70% reported to have ever used probiotics 130 . A recent Cochrane Review on the use of probiotics found a significant reduction in faecal calprotectin (a marker of intestinal inflammation) in children and adults with CF 131 .…”
Section: Introductionmentioning
confidence: 99%
“…Other mechanisms involve production of antimicrobial peptides, stimulation of resident immune cells, regulation of bile acid metabolism, and synthesis of short‐ and branched‐chain fatty acids 150 . A recent survey showed that adults living with CF frequently used probiotics, but more commonly for GI and antibiotic‐related purposes 151 . Despite being unsure about their helpfulness, many participants considered probiotics safe and used them without consulting healthcare professionals, highlighting the need for clinical trials to test the efficacy of probiotics in relieving CF GI symptoms.…”
Section: From Adolescence To Adulthoodmentioning
confidence: 99%
“…150 A recent survey showed that adults living with CF frequently used probiotics, but more commonly for GI and antibiotic-related purposes. 151 Despite being unsure about their helpfulness, many participants considered probiotics safe and used them without consulting healthcare professionals, highlighting the need for clinical trials to test the efficacy of probiotics in relieving CF GI symptoms. A few probiotic clinical trials have been conducted in CF populations but have primarily focused on respiratory outcomes, with limited attention given to GI outcomes.…”
Section: Gastrointestinal Healthmentioning
confidence: 99%